Between stigma and pink positivity: women’s perceptions of social interactions during and after breast cancer treatment - Trusson, Diane; Pilnick, Alison (Blackwell Publishing, 2017)
This study explores women’s perceptions of social interaction during and after their treatment for early stage breast cancer. Analysis of interviews with 24 women between 6 months-29 years post-diagnosis, reveals that interactions can be influenced by conflicting public discourses surrounding breast cancer. For example, there is the continuing association of cancer with death and the resulting potential for a stigmatised identity (Goffman, 1963). In contrast is the ultra-positive discourse around cancer survivorship, with breast cancer in particular being associated with pink campaigning and a push towards positive thinking. Participants described ‘managing’ conversations during treatment; sometimes playing down their ‘private’ suffering and presenting a positive (‘public’) image rather than risk alienating support. After treatment they were encouraged to move on and get back to ‘normal’. Whilst other breast cancer patients/survivors were often good sources of support, there was also a danger of assuming that all experiences will be the same. We present data to illustrate that women often present ‘public’ accounts which are driven by an expectation of positivity and fear of stigmatization at all stages of breast cancer treatment and beyond.